Discrepancies in internal and external training load measurements during low-intensity biathlon training - Kårström, Andreas; Swarén, Mikael; Björklund, Glenn (Frontiers in Sports and Active Living, 2024)
Purpose This study aimed to differentiate external and internal training loads during on-snow biathlon training by adding an accelerometer-derived metric. Methods Eleven adolescent athletes were fitted with a combined heart rate (HR) and accelerometer to be worn during all training sessions. Duration, HR, training impulse (TRIMP), and average net force (AvFNet) were used as training variables. All training was divided into either low-intensity training (LIT), or high-intensity training (HIT) based on reported intensity. The training was further categorized as training without any shooting practice (NS) or as a combination of skiing and shooting (COMB). Duration, HR, TRIMP, and AvFNet were analyzed in a linear mixed model for the different training modalities. Results All training was similar in duration for LIT and HIT sessions (p = .0521) and NS and COMB sessions (p = .988). TRIMP did not differentiate between LIT or HIT training (p = .350) or for NS compared to COMB (p = .298). While AvFNet decreased during COMB compared to NS during LIT sessions (p < .001) it remained similar during HIT training (p = 1.00). Conclusion The study’s findings indicated that there were no notable differences in internal training load (TRIMP) when comparing various training intensities and modes. However, the type of training had a significant impact on AvFNet, especially leading to a decrease during COMB sessions under LIT conditions. Incorporating an external load metric could offer a fresh approach when prescribing and evaluating training, providing deeper insights into the training load.